2018
DOI: 10.2140/apde.2018.11.1049
|View full text |Cite
|
Sign up to set email alerts
|

Scale-free unique continuation principle for spectral projectors, eigenvalue-lifting and Wegner estimates for random Schrödinger operators

Abstract: We prove a scale-free, quantitative unique continuation principle for functions in the range of the spectral projector χ (−∞,E] (H L ) of a Schrödinger operator H L on a cube of side L ∈ N, with bounded potential. Such estimates are also called, depending on the context, uncertainty principles, observability estimates, or spectral inequalities. We apply it to (i) prove a Wegner estimate for random Schrödinger operators with non-linear parameterdependence and to (ii) exhibit the dependence of the control cost o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 53 publications
(80 reference statements)
2
69
2
Order By: Relevance
“…Actually, Theorem 2.13 holds in a much more general setting, see [23]. We only mention here the (general) random breather model in which the characteristic functions of balls with random radii are replaced by random dilations of radially decreasing, compactly supported, bounded and positive function u:…”
Section: Theorem 212 ( [22 23])mentioning
confidence: 99%
“…Actually, Theorem 2.13 holds in a much more general setting, see [23]. We only mention here the (general) random breather model in which the characteristic functions of balls with random radii are replaced by random dilations of radially decreasing, compactly supported, bounded and positive function u:…”
Section: Theorem 212 ( [22 23])mentioning
confidence: 99%
“…By now there is a wealth of results pursuing the connection between unique continuation and spectral theory of random Schrödinger operators, see e.g. [6,8,2,7,26,4,21,22,3,16,28,18,19,29]. While the proofs of Theorems 2.1, 2.2 and 2.3 use in particular the guiding thread of [16], they show how this approach and the recent result of [1] complement each other in an efficient way.…”
Section: Introductionmentioning
confidence: 99%
“…More than this, there are several quantitative formulations of unique continuation which proved to be useful in a variety of applications, see e.g. [BK05,RL12,BK13,RMV13,NTTV16]. For instance, Bourgain and Kenig [BK05] showed that if ∆u = V u in R d , u(0) = 1 and u, V ∈ L ∞ (R d ) then for all x ∈ R d with |x| > 1 we have max |y−x|≤1 |u(y)| > c · exp −c ′ (log|x|)|x| 4/3 .…”
Section: Introductionmentioning
confidence: 99%
“…The full answer has been announced in [NTTV15], and full proofs have been given in [NTTV16]. There, the constant…”
Section: Introductionmentioning
confidence: 99%